Effects of different plant growth regulators as the foliar application on growth and flower quality of potted rose (Rosa chinensis Jacq. cv. Nhung) - Pham, Thi Phuong Thao; Le, Van Hoa; Le, Thanh Toan; Trinh, Van Ban (CTU Journal of Innovation and Sustainable Development, 2023)
This study was conducted to evaluate the different concentrations of Naphthalene acetic acid (NAA), Benzyladenine (BA) and Gibberellic acid (GA3) as foliar applications on growth and flower quality of potted rose Nhung (Rosa chinensis Jacq. cv. Nhung). The experiment was constructed in a completely randomized design, that included seven treatments, such as control (sprayed water), NAA, BA and GA3 at two different concentrations of 25 and 50 ppm, in six replications, with one plant/pot for each replication. The chemical solutions were applied three times at an interval of fifteen days. The results revealed that some plant growth regulators increased the growth and flowering time of rose cv. Nhung. Using pre-harvest foliar sprays of NAA and BA at 25 and 50 ppm concentrations showed maximum bud diameter, flower diameter and flowering duration as compared with the control treatment. The concentration of GA3 foliar application at 25 ppm increased plant growth (the height of flowering branches and Spad values) without affecting flower quality values and the flowering duration in comparison with the control treatment.